Commercial remedies resolving controversies - Virgo, Graham 1966-; Worthington, Sarah 1955- (Cambridge University Press, 2017)
The law of commercial remedies raises a number of important doctrinal, theoretical and practical controversies which deserve sustained and rigorous examination. This volume explores such controversies and suggests solutions, which is essential to ensure that the law is defensible, clear and just. With contributions from twenty-three leading academic and practitioner experts, this book addresses significant issues in the law which, taken together, range across the entire remedial jurisdiction as it applies to commercial disputes. The book primarily focuses on the resolution of controversies in the English law of commercial remedies, but recent developments elsewhere are also considered, especially in other common law jurisdictions. The result provides remarkably comprehensive coverage of the field which will be of relevance to academics, students, judges and practitioners
Keywords: Commercial law / England; Remedies (Law) / England